La práctica pedagógica investigativa de profundización en la licenciatura de educación básica de la facultad de estudios a distancia (2019)
This article focuses on the analysis of the Investigational Pedagogical Practice of Deepening that students of X semester of Distance Faculty realice in the Pedago- gical and Technological University of Colombia, which is constitute in the resignifi- cation and sense from disciplinary and interdisciplinary components of deepening and its pedagogical knowledge in the educational, social and cultural fields where it performs. Regulated by Resolution 37 of 2015. Its objective is to present the practice based on the skills that students develop in the course of their professional training and how they influence their teaching.